Asymmetric α-alkylation reactions,Asymmetric [alpha]-alkylation reactions - Klein, Rosalyn (Rhodes University, Faculty of Science, Department of Chemistry, 2000)
A novel camphor-derived hydroxy ketal 138 has been developed as a crural auxiliary, and used to prepare a series of six carboxylic esters of increasing steric bulk. The α-benzylation of this series of esters was achieved with diastereoselectivities of 59 - 83％ d. e. and in 39 - 48％ material yield. These results compared very favourably with those obtained in earlier studies using a regioisomeric analogue as the chiral auxiliary. Computer.modelling studies of the putative enolate intermediate has provided some insight into the possible mode of electrophilic attack at the α-carbon and the roles of the ketal protecting group and the lithium cation in these asymmetric transformations. In a related investigation, based on earlier work, a camphor-derived imino lactone has provided convenient access to α-alkyl α-amino acids, the imino lactone serving as a masked glycine equivalent. Using straight chain primary alkyl iodides [RI; R = Me, Et, Pr, Bu, CH₃(CH₂)₄ and CH₃(CH₄)₅], alkylation of the potassium enolate of the camphor-derived imino lactone was effected with 54 - 89％ d.e. and in 54 - 87％ material yield. Four novel alkylated derivatives were synthesised using isopropyl iodide, sec-butyl iodide and allyl iodide, the latter reagent resulting in both the monoallylated and diallylated products. While very good diastereoselectivities were achieved (83 - 88％ d. e.) in these reactions, the material yields from reaction with the secondary alkyl iodides were low (31- 35％) due, presumably, to their decreased electrophilicity. Computer modelling studies of the enolate were carried out and support the hypothesis of endo attack by the electrophile on the enolate intermediate. These studies also indicate the possibility of coordination of the postassium cation to the endocyclic ester oxygen, thus effectively anchoring the bulky cation away from the reaction site.
Keywords: Asymmetric synthesis; Alkylation; Chemical reactions